MIDWIFERY CARE MANAGEMENT FOR A 25-YEAR-OLD PREGNANT WOMAN (G1P0A0) WITH PREMATURE RUPTURE OF MEMBRANES (PROM) AT KLINIK PRATAMA SITI KHOLIJAH IN 2026 - Khairunnisa; Br. Ginting , Kartika Ovalina; Siregar, Erin Padilla; Pitaloka, Diah; Damayanty; Kholijah, Siti (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: The Maternal Mortality Rate (MMR) in Indonesia remains high, recorded at 189 per 100,000 live births in 2025, placing Indonesia among the countries with the highest MMR in Southeast Asia. One of the major causes of pregnancy and childbirth complications is Premature Rupture of Membranes (PROM), which can increase the risk of infection, preterm labor, and maternal and neonatal mortality. Therefore, appropriate midwifery care is essential to prevent further complications in PROM cases. Objective: This case study aims to analyze the management of midwifery care for a 25-year-old pregnant woman, Ny. R, G1P0A0, with Premature Rupture of Membranes (PROM) at Klinik Pratama Siti Kholijah. Methods: This study used a descriptive case study approach. The subject was one pregnant woman diagnosed with PROM. Data were collected through interviews, observation, physical examination, and medical record documentation. The analysis was conducted by reviewing the mother’s characteristics, pregnancy history, obstetric history, and medical history, and then comparing them with relevant theories and midwifery care standards. Results: The case study showed that the management of midwifery care for a woman with PROM was carried out through comprehensive assessment, monitoring of maternal and fetal conditions, and collaborative management according to medical indications to prevent further complications. Conclusion: Midwifery management in pregnant women with Premature Rupture of Membranes (PROM) must be performed promptly, appropriately, and comprehensively to prevent the risk of infection and complications for both mother and fetus.